Single-random phase encoding architecture using a focus tunable lens - Mosso Solano, Edward Fabián (2016)
We propose a new nonlinear optical architecture based on a focus tunable lens and an iterative phase retrieval algorithm. It constitutes a compact encryption system that uses a single-random phase key to simultaneously encrypt (decrypt) amplitude and phase data. Summarily, the information encoded in a transmittance object (phase and amplitude) is randomly modulated by a diffuser when a laser beam illuminates it; once the beam reaches a focus tunable lens, different subjective speckle distributions are registered at some image plane as the focal length is tuned to different values. This set of speckle patterns constitutes a delocalized ciphertext, which is used in an iterative phase retrieval algorithm to reconstruct a complex ciphertext. The original data are decrypted propagating this ciphertext through a virtual optical system. In this system, amplitude data are straightforwardly decrypted while phase data can only be restored if the random modulation produced in the encryption process is compensated. Thus, an encryption-decryption process and authentication protocol can simultaneously be performed. We validate the feasibility of our proposal with simulated and experimental results.